1966
DOI: 10.2307/1933765
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Leaf Litter in Relation to Environment, Microflora, and Microbial Respiration

Abstract: Bacterial and fungal counts, mycelial growth, microbial evolution of Co2, and substrate moisture and temperature in bags with litter of either mulberry, redbud, white oak, loblolly pine, or beech were measured biweekly over the period November 1960—November 1961 in oak, pine, and maple stands at Oak Ridge, Tennessee. Serial dilution plate method and closed—box technique were effective for measuring microbial densities and microbial respiration respectively. Microbial densities, microbial respiration, and annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
103
0
6

Year Published

1971
1971
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(120 citation statements)
references
References 10 publications
11
103
0
6
Order By: Relevance
“…After maggot migration, this input was associated with an increase of 1.4-2.7 μg CO 2 -C g −1 cadaver (dry weight) per hour (h −1 ) during cold seasons and 41-68 μg CO 2 -C g −1 cadaver (dry weight) h −1 during warm seasons (Putman 1976(Putman , 1978b. By comparison to other organic resources, Putman (1983) demonstrated that similar levels of CO 2 -C can evolve during the decomposition of fecal matter (millipede pellets: Glomeris marginata Villers, 1789) (Nicholson et al 1966) and plant litter (redbud leaves: Cercis canadensis L.) (Witkamp 1966). However, peak levels of microbial activity associated with fecal and plant resources tend to occur immediately after introduction to the soil when the readily available components are accessible.…”
Section: Decomposition Stages and Gravesoil Ecologymentioning
confidence: 99%
“…After maggot migration, this input was associated with an increase of 1.4-2.7 μg CO 2 -C g −1 cadaver (dry weight) per hour (h −1 ) during cold seasons and 41-68 μg CO 2 -C g −1 cadaver (dry weight) h −1 during warm seasons (Putman 1976(Putman , 1978b. By comparison to other organic resources, Putman (1983) demonstrated that similar levels of CO 2 -C can evolve during the decomposition of fecal matter (millipede pellets: Glomeris marginata Villers, 1789) (Nicholson et al 1966) and plant litter (redbud leaves: Cercis canadensis L.) (Witkamp 1966). However, peak levels of microbial activity associated with fecal and plant resources tend to occur immediately after introduction to the soil when the readily available components are accessible.…”
Section: Decomposition Stages and Gravesoil Ecologymentioning
confidence: 99%
“…The number of aerobic cellulose decomposing and nitrifying bacteria was determined (POCHON & TARDIEUX, 1962) with the MPN (Most Probable Number) method in liquid culture media. The further parameters were the soil respiration (WITKAMP, 1966. cit.…”
Section: Methodsmentioning
confidence: 99%
“…No statistically significant differences were observed between honeysuckle shrub present and removed plots within any particular date using the false discovery rate for multiple comparisons. Decomposition is a complex process that is influenced by a number of interacting factors, including regional climate (Meentemeyer 1978;Couteaux et al 1995;Aerts 1997), microclimatic conditions (Moore 1986;Hornsby et al 1995), the chemical quality of the leaf litter (Pereira et al 1998;Melillo et al 1982), and the decomposer community (Witkamp 1966;Seastedt 1984;Heneghan et al 2007). Much of our understanding of decomposition and the factors that influence it comes from studies focusing on the litter dynamics of single species (Blair et al 1990).…”
Section: Potential N Loss From Systemmentioning
confidence: 99%